Prevalence of Depressive Disorders in Operatively Treated Pelvic Trauma Patients - Piotr Walus; Jakub Ohla; Rafał Wójcicki; Tomasz Pielak; Jakub Bulski; Michał Wesołowski; Gazi Huri; Jan Zabrzyński (Diseases)
Aim: The aim of this study is to assess the prevalence of depressive disorders in patients with pelvic fractures treated surgically at our center in the years 2017–2022. Materials and Methods: The study included 75 patients, 57 men and 18 women, operated on in our center in the years 2017–2022 due to acetabular fracture and pelvic ring injury. Factors such as age, gender, chronic pain measured with the VAS scale, and the incidence of suicidal thoughts were also analyzed. The participants completed the Beck Depression Inventory (BDI). Results: Thirty-five out of the seventy-five patients showed symptoms of depression (BDI score > 11), which is 47%, with an average score of 29 (p < 0.0001). Women obtained an average BDI score of 23, which corresponds to moderate depression on Beck’s scale (p < 0.008). The correlation between BDI score and chronic pain in pelvic trauma patients has been found to be positive (p < 0.0003; r = 0.4094). Furthermore, women in our studied population reported suicidal thoughts more often than men (44% vs. 14%; p < 0.01). No statistically significant correlation was found between the occurrence of depression and the length of hospital stay and the patient’s age (p < 0.5 and p < 0.06, respectively). Conclusions: The prevalence of depression in the pelvic trauma patients of the studied population has been determined to be 47%.